The Role of Calcium and Nicotinic Acid Adenine Dinucleotide Phosphate (NAADP) in Human Osteoclast Formation and Resorption. - Cheng, X; Hookway, E; Kashima, T; Oppermann, U; Galione, A; Athanasou, N (Springer US, 2015)
Osteoclasts are specialised bone resorbing cells which form by fusion of circulating mononuclear phagocyte precursors. Bone resorption results in the release of large amounts of calcium into the extracellular fluid (ECF), but it is not certain whether changes in extracellular calcium concentration [Ca(2+)]e influence osteoclast formation and resorption. In this study, we sought to determine the effect of [Ca(2+)]e and NAADP, a potent calcium mobilising messenger that induces calcium uptake, on human osteoclast formation and resorption. CD14+ human monocytes were cultured with M-CSF and RANKL in the presence of different concentrations of calcium and NAADP and the effect on osteoclast formation and resorption evaluated. We found that the number of TRAP+ multinucleated cells and the extent of lacunar resorption were reduced when there was an increase in extracellular calcium and NAADP. This was associated with a decrease in RANK mRNA expression by CD14+ cells. At high concentrations (20 mM) of [Ca(2+)]e mature osteoclast resorption activity remained unaltered relative to control cultures. Our findings indicate that osteoclast formation is inhibited by a rise in [Ca(2+)]e and that RANK expression by mononuclear phagocyte osteoclast precursors is also [Ca(2+)]e dependent. Changes in NAADP also influence osteoclast formation, suggesting a role for this molecule in calcium handling. Osteoclasts remained capable of lacunar resorption, even at high ECF [Ca(2+)]e, in keeping with their role in physiological and pathological bone resorption.